Image-defined risk factor assessment of neurogenic tumors after neoadjuvant chemotherapy is useful for predicting intra-operative risk factors and the completeness of resection - Irtan, Sabine; Brisse, Hervé J; Minard-Colin, Véronique; Schleiermacher, Gudrun; Galmiche-Rolland, Louise; Le Cossec, Chloé; Elie, Caroline; Canale, Sandra; Michon, Jean; Valteau-Couanet, Dominique; Sarnacki, Sabine (Pediatric blood & cancer, 2015)
Background Patients with neuroblastoma are now stratified at diagnosis according to the presence and number of image‐defined risk factors (IDRFs). We examined the added value of IDRF assessment after neoadjuvant chemotherapy for predicting surgical resection. Material and Methods From 2009–2012, 39 out of 91 patients operated on in our institution for neuroblastic tumors received neoadjuvant chemotherapy based on ongoing SIOPEN protocols or treatment guidelines. IDRFs were assessed both at diagnosis and preoperatively on CT and/or MRI. Results Median age at diagnosis was 30 months [range 2–191]. The tumor locations were adrenal (n = 20), paravertebral (n = 13) and perivascular (n = 6). INRGSS stages were L2 (n = 13), M (n = 25) and Ms (n = 1). Eleven tumors (28%) were MYCN‐amplified. Chemotherapy reduced the number of IDRFs in 54% of patients overall (21/39): 61.5% (16/26) of M and Ms patients, and 38.5% (5/13) of non metastatic patients (P < 0.001). The number of IDRFs lost after chemotherapy was proportional to the degree of tumor shrinkage (P = 0.002), independent of the primary tumor location (P = 0.73), although the number was higher in patients with left versus right adrenal locations (P = 0.004). Patients with neuroblastoma on post‐surgical histology lost more IDRFs (median: 1[0–9]) than patients with ganglioneuroblastoma (median: 0[0–4]) (P < 0.001). The completeness of resection was related only to the number of preoperative IDRFs (P = 0.028). Conclusion IDRF assessment after neoadjuvant chemotherapy is useful for predicting completeness of resection of neurogenic tumors. A larger international study is needed to confirm these results and to explore a possible correlation between preoperative IDRF status and survival. Pediatr Blood Cancer 2015;62:1543–1549. © 2015 Wiley Periodicals, Inc.